Lithium ion battery and electric device
Patent Information
- Application Number
- CN202510464877.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-14
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]本申请提供的锂离子电池中,正极活性材料采用了第一活性材料磷酸铁锂或其掺杂改性材料、包覆改性材料和第二活性材料磷酸钛锂或其掺杂改性材料、包覆改性材料搭配构成,其能够有效改善传统磷酸铁锂材料在低温、低荷电状态(SOC)下性能较差的问题;同时,第一正极活性材料和第二正极活性材料以满足上述范围内平均粒径进行搭配时,有利于提升正极极片压实密度,从而兼顾改善锂离子电池的能量密度
[0004]本申请目的在于,提供一种锂离子电池,所述锂离子电池在低温、低荷电状态(SOC)下具有优异的功率性能,并兼顾具有较好的能量密度。
Smart Images

Figure BDA0005358265750000241 
Figure BDA0005358265750000251 
Figure BDA0005358265750000261
Abstract
Description
Technical Field
[0001] This application relates to the field of lithium-ion battery technology, and in particular to a lithium-ion battery and an electrical device thereof. Background Technology
[0002] In recent years, rechargeable batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric cars, military equipment, aerospace, and many other fields. With the increasing application of rechargeable batteries, higher requirements have been placed on their cycle performance and service life.
[0003] Lithium iron phosphate (LFP) cathode active materials possess advantages such as high specific capacity, high safety, and low cost, playing a crucial role in lithium-ion battery applications. However, LFP batteries exhibit poor power performance at low temperatures and low state of charge (SOC), limiting their further application. Summary of the Invention
[0004] The purpose of this application is to provide a lithium-ion battery that exhibits excellent power performance at low temperature and low state of charge (SOC) while also having good energy density.
[0005] To achieve the above objectives, a first aspect of this application provides a lithium-ion battery, comprising a positive electrode, a negative electrode, an electrolyte, and a separator between the positive and negative electrodes. The positive electrode comprises a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector. The positive electrode film layer comprises a positive active material, which comprises a first active material and a second active material. The first active material comprises lithium iron phosphate or its doped or modified materials, or its coated or modified materials, and the average particle size of the first active material is 200-500 nm. The second active material comprises lithium titanium phosphate or its doped or modified materials, or its coated or modified materials, and the average particle size of the second active material is 500-1000 nm.
[0006] The lithium-ion battery provided in this application uses a combination of a first active material (lithium iron phosphate or its doped and modified material), a coating modification material, and a second active material (lithium titanium phosphate or its doped and modified material), along with a coating modification material. This effectively improves the poor performance of traditional lithium iron phosphate materials at low temperatures and low states of charge (SOC). Furthermore, when the first and second active materials are combined to meet the average particle size requirements within the aforementioned range, it helps to increase the compaction density of the positive electrode sheet, thereby improving the energy density of the lithium-ion battery. Therefore, the lithium-ion battery provided in this application can improve power performance while also maintaining good energy density.
[0007] In any embodiment, in the cross-section of the positive electrode film layer along the thickness direction of the electrode sheet, the area ratio of particles with a particle size of 1-5 μm in the first active material is 30.0%-50.0%.
[0008] In any embodiment, in the cross-section of the positive electrode film layer along the thickness direction of the electrode sheet, the area ratio of particles with a particle size greater than 5 μm in the first active material is 0.
[0009] When the particle size of the first active material meets the above range, it is beneficial to maintain good lithium-ion transport performance of the material while increasing the compaction density of the positive electrode sheet, thereby further improving the kinetic performance and energy density of the lithium-ion battery.
[0010] In any embodiment, the Dv50 of the first active material is 0.4-1.8 μm.
[0011] In any embodiment, the Dv50 of the second active material is 1.0-2.5 μm.
[0012] When the first active material and the second active material are combined with particles within the above-mentioned range, the tap density of the material can be effectively improved, thereby achieving high tap density of the electrode and further improving the energy density of the battery.
[0013] In any embodiment, the Dv99 of the second active material is 3.0-15 μm.
[0014] When the Dv99 of the second active material is controlled within the above range, it can be better matched with the first active material. This avoids the problem that the particle size difference between the two active materials is too large, or that the particles of the second active material are too large, which would cause the positive electrode active material to easily generate scratches on the current collector under certain coating conditions, thereby improving the processing performance of the positive electrode active material.
[0015] In any embodiment, the mass ratio of the first active material to the second active material is 90:10-99:1.
[0016] By controlling the mass ratio of the first active material and the second active material within the above range, the low-temperature, low-SOC power performance and energy density of the battery can be further improved, thereby further enhancing the overall performance of the battery.
[0017] In any embodiment, the molar ratio of Li to transition metal in the second active material is (0.5-1.5):1.
[0018] When the molar ratio of Li to transition metal elements in the second active material is controlled to meet the above range, the lithium-ion concentration can be further increased, thereby further improving the energy density of the lithium-ion battery.
[0019] In any embodiment, the molar percentage of Ti element is ≥90% based on the total molar amount of transition metal elements in the second active material.
[0020] Based on the total molar amount of transition metal elements in the second active material, when the molar proportion of Ti element in the second active material is ≥90%, its specific capacity can be further improved, thereby further improving the energy density and power performance of lithium-ion batteries at low temperature and low SOC.
[0021] In any embodiment, the molar percentage of Fe element is ≥40% based on the total molar amount of transition metal elements in the first active material.
[0022] Based on the total molar amount of transition metal elements in the first active material, when the molar proportion of Fe element in the first active material is ≥40%, the power performance of lithium-ion batteries at low temperature and low SOC can be further improved.
[0023] In any embodiment, the compacted density of the positive electrode active material under 3T pressure is 2.45-2.65 g / cm³. 3 .
[0024] In any embodiment, the compaction density of the positive electrode film layer in the fully discharged state of the lithium-ion secondary battery is 2.40-2.70 g / cm³. 3 .
[0025] When the compaction density of the positive electrode active material powder and the compaction density of the positive electrode film are controlled within the above range, the energy density of the battery can be further improved.
[0026] A second aspect of this application provides an electrical device including the lithium-ion battery described in the first aspect of this application. Attached Figure Description
[0027] Figure 1 This is a schematic diagram of a secondary battery according to one embodiment of this application;
[0028] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of this application is shown;
[0029] Figure 3 This is a schematic diagram of a battery module according to one embodiment of this application;
[0030] Figure 4 This is a schematic diagram of a battery pack according to one embodiment of this application;
[0031] Figure 5 yes Figure 4 An exploded view of a battery pack according to one embodiment of this application is shown;
[0032] Figure 6 This is a schematic diagram of an electrical device that uses a secondary battery as a power source according to one embodiment of this application.
[0033] Explanation of reference numerals in the attached figures:
[0034] 1 Battery pack; 2 Upper housing; 3 Lower housing; 4 Battery module; 5 Secondary battery; 51 Housing; 52 Electrode assembly; 53 Top cover assembly. Detailed Implementation
[0035] The embodiments of the secondary battery and power-consuming device of this application are hereby disclosed in detail with appropriate reference to the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of actually identical structures may be omitted. This is to avoid making the following description unnecessarily lengthy and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0036] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0037] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0038] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0039] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0040] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0041] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0042] In conventional cathode active materials, including lithium iron phosphate or its doped and modified materials, and coated modified materials, lithium-ion insertion and extraction occur in a one-dimensional structure, resulting in low lithium-ion conductivity and consequently poor power performance at low temperatures and low state of charge (SOC). Simply using particle nano-sizing to improve ionic conductivity, or simply using carbon coating on particle surfaces to improve electronic conductivity, may lead to problems such as low volumetric energy density and poor processability of the active material. Furthermore, these methods do not effectively improve the poor power performance at low temperatures and low SOC.
[0043] This application provides a lithium-ion battery, which includes a positive electrode, a negative electrode, an electrolyte, and a separator between the positive and negative electrodes. The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector. The positive electrode film layer includes a positive active material, which includes a first active material and a second active material. The first active material includes lithium iron phosphate or its doped or modified materials, or its coated or modified materials, and the average particle size of the first active material is 200-500 nm. The second active material includes lithium titanium phosphate or its doped or modified materials, or its coated or modified materials, and the average particle size of the second active material is 500-1000 nm.
[0044] In this application, the term "particle" refers to a particle in the positive electrode film layer that has a recognizable complete boundary in the field of view at a certain magnification, such as 10,000x. Defects and scratches may exist inside the particle, but a complete boundary sufficient to divide the particle cannot be identified inside the particle.
[0045] The particle identification method is as follows: The positive electrode film layer is cut along the thickness direction of the electrode sheet using an argon ion beam (for example, a Leica EM TIC 3X CP device can be used, operating voltage: 6kV, operating time: 6h). After exposing the cut surface, a scanning electron microscope (SEM) is used (for example, a Hitachi SU8230 device can be used, operating voltage: 3kV, beam current: high, probe model: U (LA100), working distance <5mm) to observe the cut surface along the thickness direction of the positive electrode film layer. Images are acquired in secondary electron mode at a non-edge position in the cut surface of the positive electrode film layer using a field emission scanning electron microscope (after observing the electrode edge under the SEM, the field of view is adjusted to the center of the sample). Electron micrographs are taken at 10kx magnification, and the particles in the electron micrographs are analyzed using ImageJ software (1.46r, win64 version). The specific usage of ImageJ software is as follows: Load the SEM image to be analyzed, such as... Figure 1As shown, the Cellpose plugin software was used to identify particles, and manual corrections were performed based on this. ImageJ was used to read and analyze the data. The specific method for identifying particles using the Cellpose plugin software is as follows: After setting the segmentation diameter parameter (diameter in the Segmentation module) to 15 pixels and clicking "run cyto3" to identify particles, particles in the image that were not identified by the software, were not fully identified by the software, or had identification errors were manually marked. The particles in the image that were not identified by the software, were not fully identified by the software, or had identification errors mainly include the following types: 1. Particles that are too large or have scratches on their surface, making them unidentifiable or incompletely recognizable; 2. During argon ion beam cutting, scratches may be generated on the particle surface, and the software may misjudge the scratches as particle boundaries during the identification process, resulting in identification errors; 3. Particles that are too small and were not successfully identified; 4. Particles located at the edge of the electron microscope field of view, with the interior of the particle penetrated by the edge, and the morphology not being fully displayed, leading to identification errors due to partial identification replacing the whole. For the unidentified or misidentified particles mentioned above, manual calibration is performed. The specific process is as follows: 1. Delete large particles located around the edges of the scanning electron microscope that are not fully displayed. 2. Determine if any unidentified or misidentified particles have internal cracks or scratches. If no cracks or scratches are found, classify it as a single particle and manually mark it based on the observed particle boundary. 3. If cracks or scratches are found inside the particle, determine if they penetrate the particle. If not, classify it as a single particle and manually mark it. 4. If cracks or scratches penetrate the particle, determine if they are linear or irregular. 5. If the cracks or scratches are irregular, classify them as the boundary between particles and divide the particles along this boundary. 6. If the cracks or scratches are linear, perform contrast comparison. 7. If the contrast is not obvious and there is no crack-like appearance, classify it as a scratch and mark it as a single particle. 8. If the contrast is strong and there is a crack-like appearance, classify it as the boundary between particles and mark it as two particles. After manual marking, delete information irrelevant to the particles from the automatic image processing, thus completing the particle identification and marking in the image.
[0046] During the compaction process, the positive electrode film undergoes compaction along its thickness direction. Therefore, compared to the surface of the positive electrode film, the cross-section along the thickness direction provides a more accurate reflection of the actual compaction of the particles within the film on a spatial scale. In the cross-section along the thickness direction, the area ratio of particles with a diameter greater than or equal to 1 μm directly reflects the ratio of the area of some particles in that size range to the total area of the particles, thus indicating the size of the particles in that range.
[0047] It is understandable that the particles in the cross-section of the positive electrode film along the thickness direction of the electrode sheet, especially those larger than 50 nm, mainly originate from the positive electrode active material. Therefore, the embodiments of this application can accurately and objectively reflect the distribution of the particles of the first and second active materials in the electrode sheet by observing and statistically analyzing the particle area in the cross-section of the positive electrode film.
[0048] The average particle size of the first active material and the second active material can be measured using methods and equipment known in the art, for example:
[0049] (1) Following the method described above in this application, particles in the positive electrode film were identified. The images after particle identification and labeling were imported into ImageJ software for analysis. The scale was set according to the scanning electron microscope image. The particle size in the cross-section along the thickness direction of the positive electrode film was statistically analyzed using the "Feret diameter" analysis function. According to the software manual (ImageJ User Guide IJ 1.46r), the "Feret" parameter obtained from the analysis represents the maximum spacing between all parallel lines in the two-dimensional projection of the particle, thus characterizing the particle size. Since particles with a diameter less than 50 nm have a large error in the statistical process and are difficult to identify accurately, and the particle size of the conductive agent is generally less than 50 nm, which will produce a large error in the statistical results, particles with a diameter less than 50 nm are not counted in the particle size statistics process in this application. (2) Identify at least 5000 particles and obtain their respective particle sizes, so that the statistical sample size is at least greater than 5000. Then the average particle size of the first active material is: the total particle size value of the first active material divided by the total number of particles; the average particle size of the second active material is: the total particle size value of the second active material divided by the total number of particles.
[0050] In some embodiments, the average particle size of the first active material is 200-500 nm, such as 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, etc., or other unlisted values in the range of 200-500 nm.
[0051] In some embodiments, the average particle size of the second active material is 500-1000 nm, such as 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, or other unlisted values in the 500-1000 nm range.
[0052] The lithium-ion battery provided in this application uses a combination of a first active material (lithium iron phosphate or its doped and modified material), a coating modification material, and a second active material (lithium titanium phosphate or its doped and modified material), along with a coating modification material. This effectively improves the poor performance of traditional lithium iron phosphate materials at low temperatures and low states of charge (SOC). Furthermore, when the first and second active materials are combined to meet the average particle size requirements within the aforementioned range, it helps to increase the compaction density of the positive electrode sheet, thereby improving the energy density of the lithium-ion battery. Therefore, the lithium-ion battery provided in this application can improve power performance while also maintaining good energy density.
[0053] As used herein, the term “State of Charge (SOC)” has the meaning known in the art as representing the ratio of a battery’s remaining capacity to its rated capacity, typically expressed as a percentage, where SOC = 0% represents a fully discharged battery and SOC = 100% represents a fully charged battery.
[0054] [Positive electrode plate]
[0055] In some embodiments, the positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector, the positive electrode film layer including a positive active material.
[0056] In some embodiments, the positive electrode active material includes a first active material and a second active material. In some embodiments, the first active material includes lithium iron phosphate or its doped or modified form, or a coating or modified form. In some embodiments, the second active material includes lithium titanium phosphate or its doped or modified form, or a coating or modified form.
[0057] In some embodiments, in the cross-section of the positive electrode film layer along the thickness direction of the electrode sheet, the area ratio of particles with a particle size of 1-5 μm in the first active material is 30.0%-50.0%, such as 30.0%, 35.0%, 40.0%, 45.0%, 50.0%, etc., or other unlisted values within the range of 30.0%-50.0%.
[0058] The area ratio of particles with a diameter of 1-5 μm in the first active material can be measured using methods and equipment known in the art. For example, particles in the positive electrode film can be identified using the method described above in this application. After particle identification and labeling, the image is imported into ImageJ software for analysis. The scale is set according to the scanning electron microscope image. The particle size, area, sphericity, and roughness of the particles in the cross-section along the thickness direction of the positive electrode film are statistically analyzed using the "Feret diameter", "Area", "Round", and "Solidity" analysis functions. According to the software manual (ImageJ User Guide IJ 1.46r), the "Feret" parameter obtained from the analysis represents the maximum spacing between all parallel lines in the two-dimensional projection of the particle, thus characterizing the particle size; the "Area" parameter obtained represents the pixel area of the particle. Because particles smaller than 50 nm are prone to significant errors during statistical analysis and are difficult to accurately identify, and because the particle size of conductive agents is generally smaller than 50 nm, which can also introduce large errors into the statistical results, particles smaller than 50 nm are not counted in the particle size statistics process of this application, and the statistical data of particles whose AR, Round, or Solidity values are displayed as "NaN" are deleted. The sum of the "Area" parameters of particles with a diameter of 1-5 μm and the sum of the "Area" parameters of all particles are calculated and used as the area of particles with a diameter of 1-5 μm and the total area of the counted particles, respectively. The sum of the areas of particles with a diameter of 1-5 μm divided by the total area of the counted particles is used as the proportion of the area of particles with a diameter of 1-5 μm in the cross-section of the positive electrode film along the thickness direction of the electrode sheet.
[0059] In some embodiments, in the cross-section of the positive electrode film layer along the thickness direction of the electrode sheet, the area ratio of particles with a particle size greater than 5 μm in the first active material is 0.
[0060] When the particle size of the first active material meets the above range, it is beneficial to maintain good lithium-ion transport performance of the material while increasing the compaction density of the positive electrode sheet, thereby further improving the kinetic performance and energy density of the lithium-ion battery.
[0061] In some embodiments, the Dv50 of the first active material is 0.4-1.8 μm, such as 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, etc., or other unlisted values within the range of 0.4-1.8 μm.
[0062] In some embodiments, the Dv50 of the second active material is 1.0-2.5 μm, such as 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, etc., or other unlisted values in the range of 1.0-2.5 μm.
[0063] In this document, the terms "Dv50" and "Dv99" refer to the particle sizes that, in the particle size distribution, represent the cumulative volume percentages of 50% and 99%, respectively, calculated from the smallest particle size. The determination method can refer to GB / T19077-2016 Particle Size Distribution Laser Diffraction Method, and can be performed using a laser particle size analyzer such as the Mastersizer 2000E from Malvern Instruments Ltd., UK.
[0064] When the first active material and the second active material are combined with particles within the above-mentioned range, the tap density of the material can be effectively improved, thereby achieving high tap density of the electrode and further improving the energy density of the battery.
[0065] In some embodiments, the Dv99 of the second active material is 3.0-15 μm, such as 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, or other unlisted values in the range of 3.0-15 μm.
[0066] When the Dv99 of the second active material is controlled within the above range, it can be better matched with the first active material. This can avoid the problem of excessive particle size difference between the two active materials and excessively large particles of the second active material, which would cause scratches on the current collector under certain coating conditions, thereby improving the processing performance of the positive electrode active material.
[0067] In some embodiments, the mass ratio of the first active material to the second active material is 90:10-99:1, such as 90:10, 91:9, 92:8, 93:7, 94:6, 95:5, 96:4, 97:3, 98:2, 99:1, or other unlisted values within the range of 90:10-99:1.
[0068] By controlling the mass ratio of the first active material and the second active material within the above range, the low-temperature, low-SOC power performance and energy density of the battery can be further improved, thereby further enhancing the overall performance of the battery.
[0069] In some embodiments, the second active material includes lithium titanium phosphate or its doped or modified materials, or coating modified materials.
[0070] In some embodiments, the lithium titanium phosphate or its doped or coated modified materials further include one or more of the elements Mn, Cu, Cr, Zn, Pb, Co, Ni, Sr, Nb, V, Al, Na, K, Mg, Ca, and Sn.
[0071] In some implementations, the molar percentage of Ti is ≥90% based on the total molar amount of transition metal elements in the second active material.
[0072] The types and contents of elements in active materials can be tested using any method known in the art. As an example, inductively coupled plasma atomic emission spectrometry (ICP-AES) was used to test the Ti element and its content, referring to Appendix C of GB / T 33822-2017.
[0073] In some embodiments, the molar percentage of Ti element, based on the total molar amount of transition metal elements in the second active material, is 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, or any value between the two.
[0074] Based on the total molar amount of transition metal elements in the second active material, when the molar proportion of Ti element in the second active material is ≥90%, its specific capacity can be further improved, thereby further improving the energy density and power performance of lithium-ion batteries at low temperature and low SOC.
[0075] In some embodiments, the molar ratio of Li to transition metal in the second active material is (0.5-1.5):1, for example, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.36:1, 1.4:1, 1.5:1, or other unlisted values within the range of (0.5-1.5):1.
[0076] In some embodiments, the transition metal element includes Ti. In some embodiments, the molar ratio of Li to Ti in the second active material is (0.5-1.5):1.
[0077] When the molar ratio of Li to transition metal elements in the second active material is controlled to meet the above range, the lithium-ion concentration can be further increased, thereby further improving the energy density of the lithium-ion battery.
[0078] In some embodiments, the second active material has the molecular formula:
[0079] Li m Ti 2-n M n (Pz O4) a ,
[0080] Wherein, M includes at least one of Mn, Cu, Cr, Zn, Pb, Co, Ni, Sr, Nb, V, Al, Na, K, Mg, Ca, and Sn, 1≤m≤3, 0≤n≤0.2, 0≤z≤1, and 0.5≤a≤3.
[0081] In some implementations, m can be selected as 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, etc., or other unlisted values within the range of 1-3. In some implementations, n can be selected as 0, 0.05, 0.1, 0.15, 0.2, etc., or other unlisted values within the range of 0-0.2. In some implementations, z can be selected as 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, etc., or other unlisted values within the range of 0-1. In some implementations, a can be selected as 0.5, 1.0, 1.5, 2.0, 2.5, 3, etc., or other unlisted values within the range of 0.5-3.
[0082] When used herein, "having a molecular formula" is not limited to the substances represented by the molecular formula, but also includes other substances formed by further appropriate modifications based on the molecular formula, without limitation. The use of "having a molecular formula" is for ease of description only and is not intended to limit this application. It is understood that new materials or substances obtained by appropriate modifications based on the listed positive electrode active materials are also within the scope of positive electrode active materials. The aforementioned appropriate modifications refer to acceptable modification methods for positive electrode active materials, and non-limiting examples include coating modification or doping modification.
[0083] In this application, unless otherwise specified, the Li content in the listing of positive electrode active materials refers to the initial state of the material. When positive electrode active materials are applied to the positive electrode sheet in a battery system, the Li content in the positive electrode active material typically changes after charge-discharge cycles. The Li content can be measured using atomic molar content, but is not limited to this. Regarding "Li content refers to the initial state of the material," the initial state of the material refers to its state before being added to the positive electrode slurry.
[0084] In the enumeration of positive electrode active materials in this application, the oxygen (O) content is only a theoretical value. Lattice oxygen release will cause changes in the atomic molar content of oxygen, and the actual O content will fluctuate. The O content can be measured using atomic molar content, but is not limited to this.
[0085] In some embodiments, the first active material includes lithium iron phosphate or its doped or modified materials, or its coated or modified materials.
[0086] In some embodiments, the lithium iron phosphate or its doped or coated modified materials further include one or more of the elements Mn, Cu, Cr, Zn, Pb, Co, Ni, Sr, Nb, V, Al, Na, K, Mg, Ca, Ti, and B.
[0087] In some embodiments, the molar percentage of Fe element is ≥40% based on the total molar amount of transition metal elements in the first active material.
[0088] In some embodiments, the molar percentage of Fe element is 40%, 50%, 60%, 70%, 80%, 90%, 100%, or any value between the two, based on the total molar amount of transition metal elements in the first active material.
[0089] Based on the total molar amount of transition metal elements in the first active material, when the molar proportion of Fe element in the first active material is ≥40%, the power performance of lithium-ion batteries at low temperature and low SOC can be further improved.
[0090] In some embodiments, the first active material comprises materials having the molecular formula:
[0091] Li x Fe 1-y N y P j O q ,
[0092] Wherein, N includes at least one of Mn, Cu, Cr, Zn, Pb, Co, Ni, Sr, Nb, V, Al, Na, K, Mg, Ca, Ti, and B, and 0.95≤x≤1.15, 0≤y≤0.6, 0.95≤j≤1, and 3.5≤q≤4.
[0093] In some embodiments, x can be selected as 0.95, 1.00, 1.05, 1.10, 1.15, etc., or other unlisted values within the range of 0.95-1.15. In some embodiments, y can be selected as 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, etc., or other unlisted values within the range of 0-0.6. In some embodiments, j can be selected as 0.95, 0.96, 0.97, 0.98, 0.99, 1.0, etc., or other unlisted values within the range of 0.95-1. In some embodiments, q can be selected as 3.5, 3.6, 3.7, 3.8, 3.9, 4, etc., or other unlisted values within the range of 3.5-4.
[0094] In some embodiments, the compacted density of the positive electrode active material under 3T pressure is 2.45-2.65 g / cm³. 3 For example, 2.45 g / cm³ 3 2.50g / cm 3 2.55g / cm 3 2.60g / cm 3 2.65g / cm 3 etc., or 2.45-2.65 g / cm³ 3 Other values not listed within the range.
[0095] In this application, the term "powder compaction density" refers to the density of a compacted compact with a certain density and strength, formed during the external force compression process. This density is measured in g / cm³, as the powder moves and deforms, larger voids are filled, the contact area between particles increases, resulting in attractive forces between atoms and enhanced mechanical cohesion between particles. 3 .
[0096] The compaction density of the positive electrode active material powder can be measured using methods and equipment known in the art. For example, it can be measured using a compaction density instrument, referring to GB / T 24533-2009. Specifically, a certain amount of positive electrode active material is placed on a compaction mold (the mold diameter is known). The mold is hollow in the middle and has a metal disc at the top and bottom. The positive electrode active material is placed between the metal discs, and a metal cylinder is placed on top. The mold is placed on a compaction density instrument, and the pressure is set to 3T. The thickness of the positive electrode active material under 3T pressure can be read on the instrument. The compaction density of the positive electrode active material powder is ρ = m / v, where v = (S × H), m is the mass of the positive electrode active material, S is the bottom area of the mold, and H is the thickness of the positive electrode active material after compaction. When the compaction density of the positive electrode active material powder is controlled within the above range, the battery can be further improved to have a higher energy density.
[0097] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0098] In some embodiments, the positive electrode may optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a terpolymer of PVDF-tetrafluoroethylene-propylene, a terpolymer of PVDF-hexafluoropropylene-tetrafluoroethylene, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorinated acrylate resin.
[0099] In some embodiments, the positive electrode may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0100] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive electrode material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.
[0101] In some embodiments, the compaction density of the positive electrode film layer in the fully discharged state of the lithium-ion secondary battery is 2.40-2.70 g / cm³. 3 For example, 2.40 g / cm³ 3 2.45g / cm 3 2.50g / cm 3 2.55g / cm 3 2.60g / cm 3 2.65g / cm 3 2.70 g / cm 3 etc., or 2.40-2.70 g / cm³ 3 Other values not listed within the range.
[0102] In this application, the fully discharged state refers to the state after the battery is placed in a 25°C oven environment, left to stand for 2 hours, and the battery temperature is maintained at 25°C, and then discharged at a constant current of 1 / 3C to 2.5V and then discharged at a constant current of 0.1C to 2.0V.
[0103] The compaction density of the positive electrode film can be tested using methods known in the art. As an example, the battery is placed in a 25°C oven environment and left to stand for 2 hours. After the battery temperature is maintained at 25°C, the battery is discharged at a constant current of 1 / 3C to 2.5V and then discharged at a constant current of 0.1C to 2.0V. The battery is disassembled to obtain the positive electrode sheet in the fully discharged state of the lithium-ion secondary battery. The residual electrolyte is treated with dimethyl carbonate solvent, the electrode sheet is dried, and it is cut into small circular pieces with an area of S. The weight is W1, and the thickness T1 of the positive electrode sheet is measured using a micrometer. Then, the positive electrode film layer of the above-weighed electrode sheet is wiped off, the weight of the current collector is weighed and recorded as W2, and the thickness T2 of the current collector is measured using a micrometer. Then, the compaction density of the positive electrode film PD = (W1-W2) / [(T1-T2)×S].
[0104] When the compaction density of the positive electrode film is controlled within the above range, the battery can be further improved to have a higher energy density.
[0105] [Negative electrode plate]
[0106] The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.
[0107] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0108] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0109] In some embodiments, the negative electrode active material may be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0110] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0111] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0112] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0113] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.
[0114] [Electrolytes]
[0115] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not specify any particular type of electrolyte; it can be selected according to requirements.
[0116] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.
[0117] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0118] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0119] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0120] [Isolation membrane]
[0121] In some embodiments, the lithium-ion battery also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.
[0122] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0123] [Lithium-ion battery]
[0124] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.
[0125] In some embodiments, the lithium-ion battery may include an outer packaging. This outer packaging can be used to encapsulate the electrode assembly and electrolyte described above.
[0126] In some implementations, the outer packaging of a lithium-ion battery can be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of a lithium-ion battery can also be a soft pack, such as a pouch. The material of the soft pack can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0127] This application does not impose any particular limitation on the shape of the lithium-ion battery; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 1 This is an example of a square-structured lithium-ion battery 5.
[0128] In some implementations, refer to Figure 2 The outer packaging may include a housing 51 and a cover plate 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 can be placed over the opening to close the receiving cavity. Positive electrode sheets, negative electrode sheets, and a separator can be formed into an electrode assembly 52 through a winding process or a stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. The lithium-ion battery 5 may contain one or more electrode assemblies 52, which can be selected by those skilled in the art according to specific practical needs.
[0129] In some implementations, individual battery cells can be assembled into a battery module. The number of individual battery cells contained in a battery module can be one or more, and the specific number can be selected by those skilled in the art based on the application and capacity of the battery module.
[0130] Figure 3 This is battery module 4, used as an example. (See reference...) Figure 3 In battery module 4, multiple battery cells 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple battery cells 5 can be fixed in place using fasteners.
[0131] Optionally, the battery module 4 may also include a housing with a receiving space in which multiple battery cells 5 are received.
[0132] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery pack.
[0133] Figure 4 and Figure 5 This is battery pack 1 as an example. (See reference...) Figure 4 and Figure 5 The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3, with the upper body 2 covering the lower body 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0134] [Electrical appliances]
[0135] In addition, this application also provides an electrical device, which includes the lithium-ion battery provided in this application. The lithium-ion battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0136] As the electrical device, a single battery cell, a battery module, or a battery pack can be selected according to its usage requirements.
[0137] Figure 6 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of lithium-ion batteries for this device, a battery pack or battery module can be used.
[0138] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use lithium-ion batteries as their power source.
[0139] Example
[0140] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0141] I. Preparation Method
[0142] Example 1
[0143] 1) Preparation of positive electrode active materials
[0144] Preparation method of lithium titanium phosphate: Lithium carbonate, titanium dioxide, and ammonium dihydrogen phosphate (molar ratio 2.75:2:3), 5.0% (based on ammonium dihydrogen phosphate) of glucose, and an appropriate amount of water are added. The mixture is ground to ensure a fine particle size (Dv50) distribution of 0.5-0.6 μm, and then spray-dried. The spray-dried powder is placed in a sintering furnace and heated to 840℃ at a rate of 3℃ / min under a nitrogen atmosphere, held for 12 hours, and then cooled. After pulverization, Li₂ with an average particle size of 710 nm is obtained. 2.72 Ti2(PO4)3 material is used as the second active material.
[0145] Lithium iron phosphate preparation method: Lithium carbonate and iron phosphate in a molar ratio of 1.0-1.05:0.95-1.0, 4000 ppm titanium, 6% glucose and 5% polyethylene glycol are mixed evenly, and an appropriate amount of water is added and ground. By controlling the number of grinding times and time, the fine particle size Dv50 is ensured to be distributed in 0.3-0.4 μm. Spray drying is performed to obtain dried precursor powder. The spray-dried powder is placed in a sintering furnace and heated from 25°C to 450°C (first temperature) at a rate of 2°C / min under a nitrogen atmosphere, and held at this temperature for 3 h (first time t1). Then, the temperature is increased to 780°C (second temperature) at a rate of 5°C / min (second temperature), and held at this temperature for 10 h (second time t2). After the end of the process, the temperature is lowered. LiFePO4 material with an average particle size of 305 nm is obtained by air jet milling and used as the first active material.
[0146] The first active material (lithium iron phosphate) and the second active material (lithium titanium phosphate) obtained above are mixed in a mass ratio of 95:5 to obtain a composite cathode material.
[0147] 2) Preparation of positive electrode sheet
[0148] A mixture of 96.0 wt% composite cathode material, 1.5 wt% conductive carbon black, and 2.5 wt% PVDF was prepared, followed by the addition of N-methylpyrrolidone and stirring to disperse the mixture, thus forming a cathode slurry. This slurry was then coated onto aluminum foil, dried, and cold-pressed to obtain a double-sided loading of 25.0 mg / cm². 2 The positive electrode plate.
[0149] 3) Preparation of negative electrode sheet
[0150] A mixture of 95.5 wt% negative electrode active material (artificial graphite), 1.0 wt% conductive agent (conductive carbon black), 2.0 wt% binder (styrene-butadiene rubber (SBR)), and 1.5 wt% thickener (sodium carboxymethyl cellulose (CMC)) was prepared by mixing with deionized water and stirring to disperse the mixture into a negative electrode slurry. The negative electrode slurry was then coated onto both sides of a Cu foil. After coating both sides, the foil was dried, cold-pressed, slit, and sheeted to obtain the negative electrode sheet. The coating surface density was 11.0 mg / cm³. 2 .
[0151] 4) Preparation of electrolyte
[0152] The electrolyte is a lithium hexafluorophosphate solution. The electrolyte lithium salt is 1.0 mol / L lithium hexafluorophosphate (LiPF6), and the solvent is EC (ethylene carbonate) and DMC (dimethyl carbonate) in a volume ratio of 1:1.
[0153] 5) Preparation of the separating membrane
[0154] A polyethylene membrane with a thickness of 9μm was used as the diaphragm.
[0155] 6) Assembly of secondary batteries:
[0156] The positive electrode, separator, and negative electrode are stacked in sequence. The separator should be able to isolate the anode and cathode. The bare cell is obtained by winding. The bare cell is placed in the outer packaging, electrolyte is injected, and it goes through processes such as encapsulation, formation, and degassing to finally obtain a lithium-ion battery.
[0157] Example 2-3
[0158] The lithium-ion batteries of Examples 2-3 are basically similar to those of Example 1 in terms of preparation method, except that the types of the first active material or the second active material are changed, as shown in Tables 1-2.
[0159] The preparation method of the second active material LiTi2(PO4)3 in Example 2 is as follows, and the rest is the same as in Example 1:
[0160] A mixture of lithium carbonate, titanium dioxide, and ammonium dihydrogen phosphate in a molar ratio of 1.1:2:3, along with 5.0% (calculated as ammonium dihydrogen phosphate) of glucose and an appropriate amount of water, was ground to ensure a fine particle size (Dv50) distribution of 0.5-0.6 μm. The mixture was then spray-dried. The spray-dried powder was placed in a sintering furnace and heated to 850 °C at a rate of 3 °C / min under a nitrogen atmosphere for 12 hours. After cooling, the powder was pulverized to obtain a LiTi2(PO4)3 composite material with a Dv50 of 1.49 μm, which served as the second active material.
[0161] The first active material LiMn in Example 3 0.6 Fe 0.4 The preparation method of PO4 is as follows, and the rest is the same as in Example 1:
[0162] 1) Take manganese tetroxide, ferrous oxalate, LiH2PO4 and titanium dioxide into a ball mill jar, with amounts of 2.61 kg, 4 kg, 6.08 kg and 0.08 kg respectively. Add anhydrous methanol to form a raw slurry. Pour it into a ball mill and mix thoroughly. Then transfer it to a sand mill at a speed of 700-1200 rpm. When the sand milling particle size is 0.3 μm, spray dry it. Sinter the first spray-dried material at 600℃ for 10 h to obtain a sintered sample.
[0163] 2) Take 8 kg of the precursor and 0.006 kg of sucrose prepared in 1), add an appropriate amount of anhydrous methanol, disperse thoroughly in a stirring tank, and then spray dry. Sinter the sprayed sample at 760℃ for 10 h to obtain lithium manganese iron phosphate cathode material.
[0164] Examples 4-7
[0165] The lithium-ion batteries in Examples 4-7 are prepared in a manner similar to that in Example 1, except that the mass ratio of the first active material and the second active material is adjusted, as detailed in Tables 1-2.
[0166] Examples 8-11
[0167] The lithium-ion batteries in Examples 8-11 are prepared using methods basically similar to those in Example 1, except that the particle sizes of the first and second active materials are altered by changing the sintering temperature during the preparation process, as detailed in Tables 1-2.
[0168] Example 8 is the same as Example 1, except that the second temperature during the preparation of the first active material is 700°C;
[0169] Example 9 is the same as Example 1, except that the second temperature during the preparation of the first active material is 830°C;
[0170] Example 10 is the same as Example 1, except that the sintering temperature during the preparation of the second active material is 720°C;
[0171] Example 11 is the same as Example 1, except that the sintering temperature during the preparation of the second active material is 810°C.
[0172] Comparative Example 1
[0173] The lithium-ion battery of Comparative Example 1 is prepared in a similar manner to that of Example 1, except that a second active material is not used in the positive electrode active material, as detailed in Tables 1-2.
[0174] Comparative Example 2
[0175] The lithium-ion battery of Comparative Example 2 is prepared in a basically similar manner to that of Example 1, except that a different type of secondary active material, LiNi, is used in the positive electrode active material. 0.55 Co 0.12 Mn 0.33 O2 (Bangpu Recycling Technology Co., Ltd., EP16), see Tables 1-2 for details.
[0176] Comparative Examples 3-4
[0177] The lithium-ion batteries of Comparative Examples 3-4 are basically similar to those of Example 1 in terms of preparation method. The difference is that the particle size of the first active material and the second active material is changed by changing the sintering temperature in the preparation process, as shown in Tables 1-2.
[0178] Comparative Example 3 is the same as Example 1, except that the second temperature during the preparation of the first active material is 840°C;
[0179] Comparative Example 4 is the same as Example 1, except that the sintering temperature during the preparation of the second active material is 790°C.
[0180] II. Performance Testing
[0181] 1. Power performance testing method under low SOC conditions
[0182] The power performance of a battery is demonstrated by testing its DCR (Distribution Rate of Return). The method is briefly described below:
[0183] The composite cathode material was used to fabricate a pouch cell. After the pouch cell was fabricated, it underwent conventional formation. The formed cells were then subjected to discharge DCR tests at 0°C and -25°C, respectively.
[0184] After being fully charged at 25℃ and 0.33C, it is then discharged at 0.33C to 20% SOC, left to stand at 0℃ for 2 hours, and then pulsed discharged at 1.5C for 30 seconds. After being fully charged at 25℃ and 0.33C, it is then discharged at 0.33C to 10% SOC, left to stand at 0℃ for 2 hours, and then pulsed discharged at 1.5C for 30 seconds.
[0185] After being fully charged at 25℃ and 0.33C, it is then discharged at 0.33C to 20% SOC, left to stand at -25℃ for 2 hours, and then pulsed discharged at 1.5C for 30 seconds. After being fully charged at 25℃ and 0.33C, it is then discharged at 0.33C to 10% SOC, left to stand at -25℃ for 2 hours, and then pulsed discharged at 1.5C for 30 seconds.
[0186] The DCR is calculated under different conditions. The formula is DCR = (Voltage at the end of rest - Voltage after pulse discharge) / Pulse current.
[0187] 2. Energy density testing methods
[0188] For a given electrochemical energy storage device, the ratio of the energy that can be charged to the mass or volume of the energy storage medium;
[0189] The battery cells were left to stand at 25°C for 2 hours to ensure the temperature remained at 25°C. At 25°C, the battery cells were charged at 0.33C to the charging cutoff voltage of 3.65V, and then continued to be charged at this cutoff voltage under constant voltage until the current reached 0.05C, at which point charging was stopped (where C represents the rated capacity of the battery cell). After leaving the battery cells to stand at 25°C for 1 hour, they were discharged at 0.33C at 25°C to the discharge cutoff voltage of 3.65V. The total discharge energy of the battery cells was recorded as E0.
[0190] Measure the length, width, and height of the battery cell, and calculate the volume of the battery cell, V0 = length × width × height.
[0191] Battery energy density = Discharge energy of a single battery cell E0 / Volume of a single battery cell V0.
[0192] III. Analysis of Test Results for Each Embodiment and Comparative Example
[0193] Lithium-ion batteries for each embodiment and comparative example were prepared according to the above method, and various performance parameters were measured. The results are shown in Tables 1 to 3 below.
[0194] Table 1 Preparation parameters
[0195]
[0196] Table 2 Preparation parameters
[0197]
[0198] Table 3 Preparation parameters or performance parameters
[0199]
[0200] As can be seen from Examples 1-11, the positive electrode active material in the lithium-ion battery of Examples 1-11 includes a first active material and a second active material. The first active material includes lithium iron phosphate or its doped and modified materials or coating modified materials, and the average particle size of the first active material is 200-500 nm. The second active material includes lithium titanium phosphate or its doped and modified materials or coating modified materials, and the average particle size of the second active material is 500-1000 nm. Therefore, the lithium-ion battery prepared in Examples 1-11 has excellent power performance at low temperature and low SOC, and also has good energy density.
[0201] The positive electrode active material in Comparative Example 1 contains only the first active material and no second active material. A comparison between Examples 1-11 and Comparative Example 1 shows that, compared to Comparative Example 1 which only contains the first active material lithium iron phosphate or its doped and modified materials, and coating modification materials, the addition of the second active material lithium titanium phosphate or its doped and modified materials, and coating modification materials to the positive electrode active material in Examples 1-11 can effectively improve the conductivity of lithium ions, thereby improving the power performance of lithium iron phosphate batteries at low temperature and low SOC.
[0202] In Comparative Example 2, the positive electrode active material, in addition to containing the first active material, had the second active material replaced with LiNi. 0.55 Co 0.12 Mn 0.33 O2. A comparison of Example 1 and Comparative Example 2 shows that, compared to the active material in Comparative Example 2, the addition of lithium titanium phosphate or its doped / modified materials and coating / modified materials as the second active material in Example 1 can further improve the power performance of lithium iron phosphate batteries at low temperature and low SOC. Other materials (such as LiNi used in Comparative Example 2)... 0.55 Co 0.12 Mn 0.33 O2 has limited effect on improving performance at low temperatures and low SOC.
[0203] In Comparative Example 3, the average particle size of the first active material in the positive electrode exceeds the range of 200-500 nm, resulting in limited improvement in battery power performance and poor energy density. In Comparative Example 4, the average particle size of the second active material exceeds the range of 500-1000 nm, improving battery power performance, but still resulting in poor energy density. The comparison between Example 1 and Comparative Examples 3 and 4 shows that when the average particle sizes of the first and second active materials exceed the aforementioned ranges, their improvement in battery power performance is limited, and energy density is poor. Only when the average particle sizes of the first and second active materials meet the aforementioned ranges can both power performance and energy density be improved, resulting in superior overall battery performance.
[0204] As can be seen from Examples 1 and 8-11, when the Dv50 of the first active material is 0.4-1.8 μm, or when the area ratio of particles with a particle size of 1-5 μm in the first active material is 30.0%-50.0%, or when the area ratio of particles with a particle size greater than 5 μm in the first active material is 0%, or when the Dv50 of the second active material is 1.0-2.5 μm, it is possible to further improve the power performance and energy density of the battery.
[0205] As can be seen from Examples 1-3, when the molar ratio of Li to transition metal in the second active material is (0.5-1.5):1, or when the molar percentage of Ti in the second active material is ≥90% in the transition metal, or when the molar percentage of Fe in the first active material is ≥40% in the transition metal, the power performance and energy density of the battery can be further improved.
[0206] As can be seen from Examples 1, 4, and 5, when the mass ratio of the first active material to the second active material in the positive electrode active material is 90:10-99:1, the power performance and energy density of the battery can be further improved.
[0207] As can be seen from Examples 6 and 7, when the mass ratio of the first active material to the second active material in Example 6 is 85:15, the power performance of the battery is significantly improved, but the energy density of the battery is poor; when the mass ratio of the first active material to the second active material in Example 7 is 99.5:0.5, the battery has excellent energy density, but its improvement on power performance is very limited.
[0208] Therefore, as can be seen from the comparison of Examples 1, 4, 5 and Examples 6, 7, when the mass ratio of the first active material to the second active material exceeds the range of 90:10-99:1, it has a certain improvement on battery performance, but the improvement is relatively limited; while when the mass ratio of the first active material to the second active material meets the range of 90:10-99:1, it can further improve the power performance and energy density of the battery, making the overall performance of the battery better.
[0209] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A lithium-ion battery, comprising a positive electrode, a negative electrode, an electrolyte, and a separator between the positive electrode and the negative electrode, wherein the positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector, the positive electrode film layer comprising a positive active material, characterized in that, The positive electrode active material includes a first active material and a second active material, wherein... The first active material includes lithium iron phosphate or its doped or modified materials, or coated modified materials, and the average particle size of the first active material is 200-500 nm; The second active material includes lithium titanium phosphate or its doped or modified materials, or coated modified materials, and the average particle size of the second active material is 500-1000 nm.
2. The lithium-ion battery according to claim 1, characterized in that, In the cross-section of the positive electrode film layer along the thickness direction of the electrode sheet, the area ratio of particles with a particle size of 1-5 μm in the first active material is 30.0%-50.0%.
3. The lithium-ion battery according to claim 1 or 2, characterized in that, In the cross-section of the positive electrode film layer along the thickness direction of the electrode sheet, the area ratio of particles with a particle size greater than 5 μm in the first active material is 0.
4. The lithium-ion battery according to any one of claims 1-3, characterized in that, The Dv50 of the first active material is 0.4-1.8 μm.
5. The lithium-ion battery according to any one of claims 1-4, characterized in that, The Dv50 of the second active material is 1.0-2.5 μm.
6. The lithium-ion battery according to any one of claims 1-5, characterized in that, The Dv99 of the second active material is 3.0-15 μm.
7. The lithium-ion battery according to any one of claims 1-6, characterized in that, The mass ratio of the first active material to the second active material is 90:10-99:
1.
8. The lithium-ion battery according to any one of claims 1-7, characterized in that, The molar ratio of Li to transition metal in the second active material is (0.5-1.5):
1.
9. The lithium-ion battery according to any one of claims 1-8, characterized in that, Based on the total molar amount of transition metal elements in the second active material, the molar proportion of Ti element is ≥90%.
10. The lithium-ion battery according to any one of claims 1-9, characterized in that, Based on the total molar amount of transition metal elements in the first active material, the molar percentage of Fe element is ≥40%.
11. The lithium-ion battery according to any one of claims 1-10, characterized in that, The compacted density of the positive electrode active material under 3T pressure is 2.45-2.65 g / cm³. 3 .
12. The lithium-ion battery according to any one of claims 1-11, characterized in that, In the fully discharged state, the positive electrode film of the lithium-ion secondary battery has a compaction density of 2.40-2.70 g / cm³. 3 .
13. An electrical appliance, characterized in that, The lithium-ion battery includes any one of claims 1 to 12.